Buffered flame-retardant cross-linked polypropylene foam material for lithium battery pack and preparation method thereof
By using buffered flame retardant cross-linked polypropylene foaming material in lithium battery packs, combined with twin screw extruder granulation and irradiation cross-linking technology, the existing polypropylene foaming material is solved during the thermoforming and foaming process. The problem of insufficient performance has achieved high-quality lithium battery pack materials, excellent heat resistance and dimensional stability, and is suitable for new energy vehicle battery packs.
Patent Information
- Application Number
- CN202310195475.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-03-03
AI Technical Summary
During the thermoforming and foaming process, existing supercritical carbon dioxide polypropylene foaming materials have problems such as low elongation of break, low melt strength, poor temperature resistance, low production efficiency and limited product size, which is difficult to meet the lithium battery pack. High safety and high quality foam plastics demand.
Using buffered flame retardant crosslinked polypropylene foaming material, by mixing foaming masterbatch, flame retardant masterbatch, antioxidant masterbatch, compatible masterbatch, molecular weight regulator masterbatch and polypropylene rubber masterbatch. It is then granulated and irradiated cross-linked through a twin-screw extruder to form a network molecular structure, and finally foamed at high temperatures to improve the magnification and performance of the material.
It realizes the high magnification, good compression elasticity, excellent heat resistance and dimensional stability of polypropylene foaming materials, and has the advantages of light and high quality, anti-corrosion and mildew, buffering and shockproof, thermal insulation and flame retardant, and is suitable for new energy sources. Automobile battery pack, and the preparation method is simple, cheap and can be mass-produced.
Smart Images

Figure BDA0004107007440000011 
Figure BDA0004107007440000021 
Figure BDA0004107007440000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials and relates to a polypropylene foam material, and specifically relates to a buffering flame-retardant cross-linked polypropylene foam material for a lithium battery pack and a preparation method thereof. Background Art
[0002] With the vigorous development of new energy vehicles in China, the industry has also put forward higher requirements for the safety of lithium batteries. In addition to the safety of the lithium battery structure itself, higher standards are also put forward for the buffer materials in the lithium battery pack at this stage.
[0003] Polypropylene (PP) is one of the most widely used general-purpose plastics, and is favored by people due to its superior properties such as light weight, low price, and high heat resistance. In addition to the known characteristics of general foam products, it also has good thermal stability, good stress cracking resistance and dimensional stability of products at high temperatures, high toughness, high tensile strength and impact strength, suitable and soft surface, and excellent microwave adaptability.
[0004] At present, traditional supercritical carbon dioxide polypropylene foam materials have been used in battery packs to a certain extent, but due to its shortcomings such as low elongation at break and low melt strength, it is not suitable for thermoforming processing, which greatly limits its use in the field of thermoforming and foaming materials. The fundamental reason for the poor elongation at break and low melt strength of PP is that it has a soft long-chain macromolecular structure and a high tendency to crystallize. Its softening point is very close to its melting point. After reaching the melting crystallization temperature, its melt viscosity drops rapidly, and a large amount of crystallization heat is released during the crystallization process, which further reduces its melt viscosity and melt strength. Therefore, PP cannot obtain a high elongation at break during the thermoforming process. During the foaming process, the gas is easy to escape and gather, and the bubble wall cannot withstand the bubble pressure and collapses and breaks, making it difficult to obtain high-quality foam plastics; and the material itself has no cross-linking degree, and its temperature resistance is relatively poor. It is extremely easy to shrink when heated, which poses a risk to the safety of lithium battery packs; the most critical thing is that this production method is inefficient and the material size is limited, resulting in great waste on the client side. Therefore, the present invention needs to improve the problems of low temperature resistance, low elongation at break, low production efficiency, and limited product size of supercritical carbon dioxide foamed polypropylene materials. Summary of the invention
[0005] In view of the defects of the above-mentioned prior art, the present invention provides a buffering flame-retardant cross-linked polypropylene foam material for lithium battery packs.
[0006] To achieve the above object, the present invention provides a buffer flame retardant cross-linked polypropylene foam material for lithium battery packs, which comprises the following raw material components in percentage by weight:
[0007]
[0008]
[0009] The foaming masterbatch contains polypropylene resin and foaming agent in a mass ratio of 1.8 to 2.5:1;
[0010] The flame retardant masterbatch contains polypropylene resin, flame retardant, antioxidant and coupling agent, the mass ratio of the polypropylene resin to the flame retardant is 1.8-2.5:1, the mass of the antioxidant is 0.2-1% of the mass of the flame retardant masterbatch, and the mass of the coupling agent is 0.5-2% of the mass of the flame retardant masterbatch;
[0011] The antioxidant masterbatch contains polypropylene resin, antioxidant and stabilizer in a mass ratio of 4 to 6:1:1;
[0012] The compatibilizer masterbatch contains polypropylene resin and a compatibilizer, and the mass content of the compatibilizer in the compatibilizer masterbatch is 5 to 20%;
[0013] The molecular weight regulator masterbatch contains polypropylene resin and molecular weight regulator, and the mass content of the molecular weight regulator in the compatibilizer masterbatch is 5 to 20%;
[0014] The polypropylene rubber masterbatch contains polypropylene resin and rubber, and the mass content of the rubber in the polypropylene rubber masterbatch is 10-30%.
[0015] Optimally, the foaming masterbatch is prepared according to the following steps: the foaming agent and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder;
[0016] The flame retardant masterbatch is prepared according to the following steps: the flame retardant, antioxidant, coupling agent and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder;
[0017] The antioxidant masterbatch is prepared according to the following steps: the antioxidant, stabilizer and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder;
[0018] The compatibilizer masterbatch is prepared according to the following steps: the compatibilizer and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder;
[0019] The molecular weight regulator masterbatch is prepared according to the following steps: the molecular weight regulator and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder;
[0020] The polypropylene rubber masterbatch is prepared according to the following steps: rubber and polypropylene resin particles are mixed in proportion and then pelletized by a twin-screw extruder;
[0021] The working temperatures of the twin-screw extruder are independently: 155±5°C for zone one, 165±5°C for zone two, 165±5°C for zone three, 170±5°C for zone four, 170±5°C for zone five, and 165±5°C for zone six.
[0022] Furthermore, the foaming agent is a mixture of one or more selected from inorganic foaming agents and organic foaming agents, the inorganic foaming agent includes calcium carbonate, magnesium carbonate, sodium bicarbonate and ammonium nitrite, and the organic foaming agent includes N,N'-dinitrosopentamethylenetetramine, azoaminobenzene, azodicarbonamide, azobisethylbutyronitrile, barium azodicarboxylate, azodicarboxylic acid esters, dinitrosopentamethylenetetramine, trinitrosotrimethylenetriamine, 4,4'-oxybisbenzenesulfonylhydrazine, toluenesulfonylsemicarbazide, triphosphorus-based triazine and 5-phenyltetrazole; when the foaming agent is a powder, its particle size is 2-25 μm.
[0023] Furthermore, the flame retardant is a mixture of one or more selected from antimony trioxide, decabromodiphenylethane, aluminum hydroxide, magnesium hydroxide, borate and molybdenum trioxide, the antioxidant is antioxidant 1010, and the coupling agent is a mixture of one or more selected from silane coupling agents and titanate coupling agents.
[0024] Further, the antioxidant is a mixture of one or more selected from the group consisting of antioxidant 1010, antioxidant 2246, antioxidant 3114, antioxidant 168, antioxidant T501, antioxidant 618, antioxidant B215, antioxidant B225, antioxidant B900, hindered phenol antioxidant 1076 and hindered amine antioxidant 944, and the stabilizer is a mixture of one or more selected from the group consisting of light stabilizer MD-1024, hindered phenol light stabilizer MD-3114 and hindered amine light stabilizer 770.
[0025] Furthermore, the compatibilizer is selected from maleic anhydride modified compatibilizers.
[0026] Furthermore, the molecular weight regulator masterbatch is prepared according to the following method: the molecular weight regulator is a mixture of one or more selected from benzoyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane.
[0027] Furthermore, the rubber is a mixture of one or more selected from SBR, BR, CR, EPDM, EBS, SEBS and NBR.
[0028] Optimally, the polypropylene resin particles are copolymers having a melt index (MI) of 1-5 g / min.
[0029] Another object of the present invention is to provide a method for preparing the buffer flame-retardant cross-linked polypropylene foam material for lithium battery packs, comprising the following steps:
[0030] (a) mixing the foaming masterbatch, the flame retardant masterbatch, the antioxidant masterbatch, the compatibilizer masterbatch, the molecular weight regulator masterbatch and the polypropylene rubber masterbatch in proportion and extruding the mixed masterbatch through a twin-screw extruder, wherein the operating temperature of the twin-screw extruder is: 155±5°C in zone 1, 165±5°C in zone 2, 165±5°C in zone 3, 170±5°C in zone 4, 170±5°C in zone 5 and 165±5°C in zone 6;
[0031] (b) subjecting the mixed master sheet to radiation cross-linking, wherein the radiation cross-linking dose is 30-120 kGy;
[0032] (c) foaming the mixed mother sheet after radiation crosslinking, wherein the foaming temperature is 220-300°C.
[0033] Due to the application of the above technical scheme, the present invention has the following advantages compared with the prior art: the buffered flame-retardant cross-linked polypropylene foam material for lithium battery packs of the present invention can form a network structure of molecular chains by mixing foaming masterbatch, flame-retardant masterbatch, antioxidant masterbatch, compatibilizer masterbatch, molecular weight regulator masterbatch and polypropylene rubber masterbatch, so that the ratio of the polypropylene foam material is 5-30 times, the compression resilience is good, and it can pass the HF-1 test; the obtained polypropylene foam material has excellent performance, and the heat resistance, dimensional stability, material strength, etc. are higher than those of molded foamed polypropylene materials; when used in new energy vehicle battery packs, it has the advantages of light weight, high strength, corrosion resistance, mildew resistance, buffering and shockproof, heat insulation and flame retardancy. The preparation method of the buffered flame-retardant cross-linked polypropylene foam material for lithium battery packs is relatively simple, cheap, and can be mass-produced, and has high economic value. DETAILED DESCRIPTION
[0034] The buffer flame-retardant cross-linked polypropylene foam material for lithium battery packs of the present invention comprises the following raw material components in percentage by weight: 5-25wt% of foaming masterbatch; 6-12wt% of flame-retardant masterbatch; 0.3-2wt% of antioxidant masterbatch; 0.3-2wt% of compatibilizer masterbatch; 0.3-2wt% of molecular weight regulator masterbatch; 60-80wt% of polypropylene rubber masterbatch; the foaming masterbatch contains polypropylene resin and foaming agent, and the mass ratio thereof is 1.8-2.5:1; the flame-retardant masterbatch contains polypropylene resin, flame retardant, antioxidant and coupling agent, and the mass ratio of the polypropylene resin to the flame retardant is 1.8-2.5:1, the mass of the antioxidant is 0.2-1% of the mass of the flame-retardant masterbatch, and the mass of the coupling agent is The flame retardant masterbatch contains 0.5-2% of the mass of the flame retardant masterbatch; the antioxidant masterbatch contains polypropylene resin, antioxidant and stabilizer, and the mass ratio is 4-6:1:1; the compatibilizer masterbatch contains polypropylene resin and compatibilizer, and the mass content of the compatibilizer in the compatibilizer masterbatch is 5-20%; the molecular weight regulator masterbatch contains polypropylene resin and molecular weight regulator, and the mass content of the molecular weight regulator in the compatibilizer masterbatch is 5-20%; the polypropylene rubber masterbatch contains polypropylene resin and rubber, and the mass content of the rubber in the polypropylene rubber masterbatch is 10-30% (the above-mentioned polypropylene resin preferably uses polypropylene resin particles, that is, polypropylene particles, and its melt index MI is a copolymer of 1-5g / min). By mixing foaming masterbatch, flame retardant masterbatch, antioxidant masterbatch, compatibilizer masterbatch, molecular weight regulator masterbatch and polypropylene rubber masterbatch, the molecular chains can form a network structure through extrusion and irradiation, and finally through high-temperature foaming, the polypropylene foam material has a ratio of 5-30 times. The material has good compression resilience and can pass the HF-1 test.
[0035] The foaming masterbatch is prepared by the following method: the foaming agent and the polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; the working temperature of the twin-screw extruder is: 155±5℃ in zone 1, 165±5℃ in zone 2, 165±5℃ in zone 3, 170±5℃ in zone 4, 170±5℃ in zone 5 and 165±5℃ in zone 6. The foaming agent is a mixture of one or more selected from inorganic foaming agents and organic foaming agents, the inorganic foaming agent includes calcium carbonate, magnesium carbonate, sodium bicarbonate and ammonium nitrite, and the organic foaming agent includes N,N'-dinitrosopentamethylenetetramine, azoaminobenzene, azodicarbonamide, azobisethylbutyronitrile, barium azodicarboxylate, azodicarboxylic acid ester, dinitrosopentamethylenetetramine, trinitrosotrimethylenetriamine, 4,4'-oxybisbenzenesulfonylhydrazide, toluenesulfonylsemicarbazide, triphosphorus-based triazine and 5-phenyltetrazole. When the foaming agent is in powder form, the particle size thereof is 2-25 μm.
[0036] The flame retardant masterbatch is prepared by the following method: flame retardant, antioxidant, coupling agent and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; the working temperature of the twin-screw extruder is: 155±5℃ in zone 1, 165±5℃ in zone 2, 165±5℃ in zone 3, 170±5℃ in zone 4, 170±5℃ in zone 5 and 165±5℃ in zone 6. The flame retardant is a mixture of one or more selected from antimony trioxide, decabromodiphenylethane, aluminum hydroxide, magnesium hydroxide, borate and molybdenum trioxide, the antioxidant is antioxidant 1010, and the coupling agent is a mixture of one or more selected from silane coupling agents (such as commercially available KH560, KH570, etc.) and titanate coupling agents (such as commercially available coupling agents TBT, coupling agent TPT, etc.).
[0037] The antioxidant masterbatch is prepared by the following method: the antioxidant, the stabilizer and the polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; the working temperature of the twin-screw extruder is: 155±5℃ in zone 1, 165±5℃ in zone 2, 165±5℃ in zone 3, 170±5℃ in zone 4, 170±5℃ in zone 5 and 165±5℃ in zone 6. The antioxidant is a mixture of one or more selected from antioxidant 1010, antioxidant 2246, antioxidant 3114, antioxidant 168, antioxidant T501, antioxidant 618, antioxidant B215, antioxidant B225, antioxidant B900, hindered phenol antioxidant 1076 and hindered amine antioxidant 944; the stabilizer is a mixture of one or more selected from light stabilizer MD-1024, hindered phenol light stabilizer MD-3114 and hindered amine light stabilizer 770.
[0038] The compatibilizer masterbatch is prepared by the following method: the compatibilizer and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; the working temperature of the twin-screw extruder is: 155±5°C in zone 1, 165±5°C in zone 2, 165±5°C in zone 3, 170±5°C in zone 4, 170±5°C in zone 5, and 165±5°C in zone 6. The compatibilizer is selected from maleic anhydride modified compatibilizers.
[0039] The molecular weight regulator masterbatch is prepared by the following method: the molecular weight regulator and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; the working temperature of the twin-screw extruder is: 155±5°C in zone 1, 165±5°C in zone 2, 165±5°C in zone 3, 170±5°C in zone 4, 170±5°C in zone 5, and 165±5°C in zone 6. The molecular weight regulator masterbatch is prepared by the following method: the molecular weight regulator is a mixture of one or more selected from benzoyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane.
[0040] The polypropylene rubber masterbatch is prepared by the following method: rubber and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; the working temperature of the twin-screw extruder is: zone 1 155±5°C, zone 2 165±5°C, zone 3 165±5°C, zone 4 170±5°C, zone 5 170±5°C, zone 6 165±5°C. The rubber is a mixture of one or more selected from SBR, BR, CR, EPDM, EBS, SEBS and NBR.
[0041] The preparation method of the buffer flame-retardant cross-linked polypropylene foam material for lithium battery packs comprises the following steps: (a) mixing the foaming masterbatch, the flame-retardant masterbatch, the antioxidant masterbatch, the compatibilizer masterbatch, the molecular weight regulator masterbatch and the polypropylene rubber masterbatch in proportion and extruding the mixed masterbatch through a twin-screw extruder, wherein the working temperature of the twin-screw extruder is: 155±5°C in zone 1, 165±5°C in zone 2, 165±5°C in zone 3, 170±5°C in zone 4, 170±5°C in zone 5 and 165±5°C in zone 6; (b) irradiating and cross-linking the mixed masterbatch, wherein the dose of the irradiation and cross-linking is 30-120 kGy; (c) foaming the mixed masterbatch after irradiation and cross-linking, wherein the foaming temperature is 220-300°C. The irradiation and cross-linking is performed by an electron accelerator, and the foaming is performed by a foaming furnace. The preparation method is relatively simple, inexpensive, and can be mass-produced, and has high economic value.
[0042] The preferred embodiments of the present invention are described in detail below.
[0043] Example 1
[0044] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof. First, various masterbatches are prepared:
[0045] (1) Preparing foaming masterbatch: uniformly mixing a foaming agent (AC foaming agent, light yellow crystalline powder, particle size of 2-25 μm) into polypropylene resin particles (i.e., uniformly stirring the foaming agent and polypropylene resin particles; the polypropylene resin particles are copolymers with a melt index of MI 1-5 g / min, brand T30S, the same below), and then granulating them through a twin-screw extruder (the operating temperature of the twin-screw extruder is: zone 1 155±5°C, zone 2 165±5°C, zone 3 165±5°C, zone 4 170±5°C, zone 5 170±5°C, zone 6 165±5°C), wherein the foaming agent accounts for 33 wt% of the foaming masterbatch content (at this time, the mass ratio of the foaming agent to the polypropylene resin particles is about 1:2);
[0046] (2) Preparation of flame retardant masterbatch: The preparation method of flame retardant masterbatch is basically the same as that of foaming masterbatch, except that flame retardant (antimony trioxide), antioxidant (antioxidant 1010), coupling agent (silane coupling agent KH560) and polypropylene resin particles are uniformly mixed, the mass ratio of flame retardant to polypropylene resin particles is 1:2, the content of antioxidant is 0.3wt% of the content of flame retardant masterbatch, and the content of silane coupling agent KH560 is 0.5wt% of the content of flame retardant masterbatch;
[0047] (3) Preparation of antioxidant masterbatch: The preparation method of antioxidant masterbatch is basically the same as that of foaming masterbatch, except that the antioxidant (a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1), stabilizer (light stabilizer MD-1024) and polypropylene resin particles are uniformly mixed in a mass ratio of 4:1:1;
[0048] (4) Preparation of compatibilizer masterbatch: The preparation method of the compatibilizer masterbatch is basically the same as the preparation method of the foaming masterbatch, except that the compatibilizer (compatibilizer CMG9801) and the polypropylene resin particles are uniformly mixed so that the content of the compatibilizer in the compatibilizer masterbatch is 8 wt %;
[0049] (5) Preparation of molecular weight regulator masterbatch: The preparation method of the molecular weight regulator masterbatch is basically the same as the preparation method of the foaming masterbatch, except that the molecular weight regulator (benzoyl peroxide, BPO) and the polypropylene resin particles are uniformly mixed so that the content of the molecular weight regulator in the compatibilizer masterbatch is 5wt%;
[0050] (6) Preparation of polypropylene rubber masterbatch (i.e., polypropylene / rubber masterbatch): The preparation method of polypropylene rubber masterbatch is basically the same as the preparation method of foaming masterbatch, except that the rubber (rubber SBR) and polypropylene resin particles are uniformly mixed so that the rubber content in the polypropylene rubber masterbatch is 20wt%.
[0051] The preparation method of the above foaming material comprises the following steps:
[0052] (a) mixing the foaming masterbatch, flame retardant masterbatch, antioxidant masterbatch, compatibilizer masterbatch, molecular weight regulator masterbatch and polypropylene rubber masterbatch in proportion (specifically: 15 kg foaming masterbatch, 10 kg flame retardant masterbatch, 2 kg antioxidant masterbatch, 2 kg compatibilizer masterbatch, 2 kg molecular weight regulator masterbatch and 69 kg polypropylene rubber masterbatch) and extruding the mixed masterbatch through a twin-screw extruder, the operating temperature of the twin-screw extruder is: 155±5°C in zone 1, 165±5°C in zone 2, 165±5°C in zone 3, 170±5°C in zone 4, 170±5°C in zone 5 and 165±5°C in zone 6;
[0053] (b) placing the mixed master sheet in an electron irradiation accelerator for irradiation cross-linking, with an irradiation dose of 85 kGy;
[0054] (c) adding the mixed mother sheet after radiation crosslinking into a foaming furnace for foaming, wherein the foaming temperature is 220-300° C.
[0055] The obtained foaming material was subjected to performance tests, and the test items, test standards and test results are listed in Table 1.
[0056] Table 1 Test table of foaming material in Example 1
[0057] Apparent density <![CDATA[g / m 3 ]]> ISO845 100 Compressive strength (25%) Kpa ISO3380-1 64 Tensile strength (MD) Kpa ISO1926 2433 Tensile strength (CD) Kpa ISO1926 1294 Elongation at break (MD) % ISO1926 607 Elongation at break (CD) % ISO1926 453 Dimensional change MD (120℃×60min) % FBS method -0.6 Dimension change CD (120℃×60min) % FBS method -0.5
[0058] Example 2
[0059] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof, which is basically the same as that in Example 1, except that: 19.5 kg of foaming masterbatch, 12 kg of flame-retardant masterbatch, 2 kg of antioxidant masterbatch, 2 kg of compatibilizer masterbatch, 2 kg of molecular weight regulator masterbatch, and 62.5 kg of polypropylene rubber masterbatch.
[0060] The obtained foaming material was subjected to performance tests, and the test items, test standards and test results are listed in Table 2.
[0061] Table 2 Test table of foaming materials in Example 2
[0062] Apparent density <![CDATA[g / m 3 ]]> ISO845 65 Compressive strength (25%) Kpa ISO3380-1 110 Tensile strength (MD) Kpa ISO1926 1310 Tensile strength (CD) Kpa ISO1926 1007 Elongation at break (MD) % ISO1926 365 Elongation at break (CD) % ISO1926 285 Dimensional change MD (120℃×60min) % FBS method -0.3 Dimension change CD (120℃×60min) % FBS method -0.2
[0063] Example 3
[0064] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof, which is basically the same as that in Example 1, except that: 22 kg of foaming masterbatch, 12 kg of flame-retardant masterbatch, 2 kg of antioxidant masterbatch, 2 kg of compatibilizer masterbatch, 2 kg of molecular weight regulator masterbatch, and 60 kg of polypropylene / rubber masterbatch.
[0065] The obtained foaming material was subjected to performance tests, and the test items, test standards and test results are listed in Table 3.
[0066] Table 3 Test table of foaming material in Example 3
[0067]
[0068]
[0069] Example 4
[0070] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof, which is basically the same as that in Example 1, except that: 9 kg of foaming masterbatch, 10.1 kg of flame-retardant masterbatch, 0.3 kg of antioxidant masterbatch, 0.3 kg of compatibilizer masterbatch, 0.3 kg of molecular weight regulator masterbatch, and 80 kg of polypropylene / rubber masterbatch.
[0071] Table 4 Test table of foaming materials in Example 4
[0072] Apparent density <![CDATA[g / m 3 ]]> ISO845 160 Compressive strength (25%) Kpa ISO3380-1 240 Tensile strength (MD) Kpa ISO1926 2557 Tensile strength (CD) Kpa ISO1926 1920 Elongation at break (MD) % ISO1926 205 Elongation at break (CD) % ISO1926 216 Dimensional change MD (120℃×60min) % FBS method -0.1 Dimension change CD (120℃×60min) % FBS method -0.1
[0073] Example 5
[0074] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof, which is basically the same as that in Example 1, except that: 5kg of foaming masterbatch, 12kg of flame-retardant masterbatch, 1kg of antioxidant masterbatch, 1kg of compatibilizer masterbatch, 1kg of molecular weight regulator masterbatch, and 80kg of polypropylene / rubber masterbatch.
[0075] Table 5 Test table of foaming material in Example 5
[0076] Apparent density <![CDATA[g / m 3 ]]> ISO845 330 Compressive strength (25%) Kpa ISO3380-1 - Tensile strength (MD) Kpa ISO1926 4273 Tensile strength (CD) Kpa ISO1926 2635 Elongation at break (MD) % ISO1926 460 Elongation at break (CD) % ISO1926 320 Dimensional change MD (120℃×60min) % FBS method -0.1 Dimension change CD (120℃×60min) % FBS method -0.1
[0077] Comparative Example 1
[0078] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof, which is basically the same as that in Example 1, except that the polypropylene material used is a copolymer (commercially available) with a melt index MI of 6-10 g / min.
[0079] Table 6 Test table of foaming material in comparative example 1
[0080] Apparent density <![CDATA[g / m 3 ]]> ISO845 100 Compressive strength (25%) Kpa ISO3380-1 45 Tensile strength (MD) Kpa ISO1926 1683 Tensile strength (CD) Kpa ISO1926 912 Elongation at break (MD) % ISO1926 429 Elongation at break (CD) % ISO1926 317 Dimensional change MD (120℃×60min) % FBS method -0.8 Dimension change CD (120℃×60min) % FBS method -0.65
[0081] Comparative Example 2
[0082] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof, which is basically the same as that in Example 1, except that it does not contain a compatibilizer masterbatch.
[0083] Table 7 Test table of foaming material in comparative example 2
[0084] Apparent density <![CDATA[g / m 3 ]]> ISO845 100 Compressive strength (25%) Kpa ISO3380-1 48 Tensile strength (MD) Kpa ISO1926 1800 Tensile strength (CD) Kpa ISO1926 971 Elongation at break (MD) % ISO1926 456 Elongation at break (CD) % ISO1926 338 Dimensional change MD (120℃×60min) % FBS method -0.3 Dimension change CD (120℃×60min) % FBS method -0.3
[0085] Comparative Example 3
[0086] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof, which is basically the same as that in Example 1, except that it does not contain a molecular weight regulator masterbatch.
[0087] Table 8 Test table of foaming material in comparative example 3
[0088]
[0089]
[0090] Comparative Example 4
[0091] This embodiment provides a buffered flame-retardant cross-linked polypropylene foam material for a new energy vehicle lithium battery pack and a preparation method thereof, which is basically the same as that in Example 1, except that it does not contain polypropylene rubber masterbatch and ultimately no foamed product can be obtained.
[0092] The foamed samples of Examples 1-5 all met the HF-1 flame retardant requirements after being sent for testing. Comparative Example 1 selected PP with a larger melt index, resulting in reduced compressive strength and tensile strength, increased dimensional shrinkage, and unchanged flame retardant performance; Comparative Example 2 did not contain a compatibilizer masterbatch, resulting in reduced compressive strength and tensile strength, and flame retardant performance failed to pass HF-1; Comparative Example 3 did not contain a molecular weight regulator masterbatch, resulting in increased material density, slightly weakened mechanical properties, and unchanged flame retardant performance.
[0093] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A buffer flame-retardant cross-linked polypropylene foam material for lithium battery packs, characterized in that: It is composed of the following raw material components in weight percentage: Foaming masterbatch 5~25wt%; Flame retardant masterbatch 6~12wt%; Antioxidant masterbatch 0.3~2wt%; Compatibilizer masterbatch 0.3~2wt%; Molecular weight regulator masterbatch 0.3~2wt%; Polypropylene rubber masterbatch 60~80wt%; The foaming masterbatch contains polypropylene resin and foaming agent, and the mass ratio thereof is 1.8-2.5:1; The flame retardant masterbatch contains polypropylene resin, flame retardant, antioxidant and coupling agent, the mass ratio of the polypropylene resin to the flame retardant is 1.8-2.5:1, the mass of the antioxidant is 0.2-1% of the mass of the flame retardant masterbatch, and the mass of the coupling agent is 0.5-2% of the mass of the flame retardant masterbatch; the flame retardant is a mixture of one or more selected from antimony trioxide, decabromodiphenylethane, aluminum hydroxide, magnesium hydroxide, borate and molybdenum trioxide; The antioxidant masterbatch contains polypropylene resin, antioxidant and stabilizer in a mass ratio of 4-6:1:1; The compatibilizer masterbatch contains polypropylene resin and a compatibilizer, and the mass content of the compatibilizer in the compatibilizer masterbatch is 5-20%; the compatibilizer is a maleic anhydride modified compatibilizer; The molecular weight regulator masterbatch contains polypropylene resin and molecular weight regulator, and the mass content of the molecular weight regulator in the compatibilizer masterbatch is 5-20%; The polypropylene rubber masterbatch contains polypropylene resin and rubber, and the mass content of the rubber in the polypropylene rubber masterbatch is 10-30%; The rubber is a mixture of one or more selected from SBR, BR, CR, EPDM, EBS, SEBS and NBR.
2. The buffer flame-retardant cross-linked polypropylene foam material for lithium battery pack according to claim 1, characterized in that: The foaming masterbatch is prepared according to the following steps: the foaming agent and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; The flame retardant masterbatch is prepared according to the following steps: the flame retardant, antioxidant, coupling agent and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; The antioxidant masterbatch is prepared according to the following steps: the antioxidant, stabilizer and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; The compatibilizer masterbatch is prepared according to the following steps: the compatibilizer and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; The molecular weight regulator masterbatch is prepared according to the following steps: the molecular weight regulator and polypropylene resin particles are mixed in proportion and then granulated by a twin-screw extruder; The polypropylene rubber masterbatch is prepared according to the following steps: rubber and polypropylene resin particles are mixed in proportion and then pelletized by a twin-screw extruder; The working temperatures of the twin-screw extruder are independently: 155±5°C for zone one, 165±5°C for zone two, 165±5°C for zone three, 170±5°C for zone four, 170±5°C for zone five, and 165±5°C for zone six.
3. The buffer flame-retardant cross-linked polypropylene foam material for lithium battery pack according to claim 2, characterized in that: The foaming agent is a mixture of one or more selected from inorganic foaming agents and organic foaming agents, wherein the inorganic foaming agent includes calcium carbonate, magnesium carbonate, sodium bicarbonate and ammonium nitrite, and the organic foaming agent includes N,N'-dinitrosopentamethylenetetramine, azoaminobenzene, azodicarbonamide, azobisethylbutyronitrile, barium azodicarboxylate, azodicarboxylic acid esters, dinitrosopentamethylenetetramine, trinitrosotrimethylenetriamine, 4,4'-oxybisbenzenesulfonylhydrazide, toluenesulfonyl semicarbazide, triphosphorus-based triazine and 5-phenyltetrazole; when the foaming agent is a powder, its particle size is 2-25 μm.
4. The buffer flame-retardant cross-linked polypropylene foam material for lithium battery pack according to claim 2, characterized in that: The antioxidant is antioxidant 1010, and the coupling agent is a mixture of one or more selected from silane coupling agents and titanate coupling agents.
5. The buffer flame-retardant cross-linked polypropylene foam material for lithium battery pack according to claim 2, characterized in that: The antioxidant is a mixture of one or more selected from the group consisting of antioxidant 1010, antioxidant 2246, antioxidant 3114, antioxidant 168, antioxidant T501, antioxidant 618, antioxidant B215, antioxidant B225, antioxidant B900, hindered phenol antioxidant 1076 and hindered amine antioxidant 944; the stabilizer is a mixture of one or more selected from the group consisting of light stabilizer MD-1024, hindered phenol light stabilizer MD-3114 and hindered amine light stabilizer 770.
6. The buffer flame-retardant cross-linked polypropylene foam material for lithium battery pack according to claim 2, characterized in that: The molecular weight regulator masterbatch is prepared according to the following method: the molecular weight regulator is a mixture of one or more selected from benzoyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane.
7. The buffer flame-retardant cross-linked polypropylene foam material for lithium battery pack according to claim 1, characterized in that: The melt index MI of the polypropylene resin particles is 1-5 g / min.
8. The method for preparing the buffer flame-retardant cross-linked polypropylene foam material for lithium battery packs according to any one of claims 1 to 7, characterized in that: The following steps are involved: (a) the foaming masterbatch, the flame retardant masterbatch, the antioxidant masterbatch, the compatibilizer masterbatch, the molecular weight regulator masterbatch and the polypropylene rubber masterbatch are mixed in proportion and then extruded through a twin-screw extruder to obtain a mixed masterbatch, wherein the operating temperature of the twin-screw extruder is: 155±5°C for zone 1, 165±5°C for zone 2, 165±5°C for zone 3, 170±5°C for zone 4, 170±5°C for zone 5 and 165±5°C for zone 6; (b) subjecting the mixed master sheet to radiation cross-linking, wherein the radiation cross-linking has a dose of 30-120 kGy; (c) foaming the mixed mother sheet after radiation crosslinking, wherein the foaming temperature is 220-300° C.
